A sign of affection. 9 - Dashiell, Christine, 1984-; Vanstiphout, Carl; Blakeslee, Lys, 1985- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2024)
Emma's relentless pursuit of Itsuomi has hit a wall, and Shin is left to pick up the pieces, if Emma will let him. Meanwhile, Oushi-kun's sudden confession makes Yuki anxious about Itsuomi's feelings. Just as the two seem to have their respective third wheels under control, Itsuomi makes a stunning suggestion: Will Yuki come and live with him? It takes courage for Yuki to admit why she's hesitant. But the clock is ticking down to Itsuomi's graduation, and his trip abroad. Yuki decides to overcome her fears of being a burden and accept. What new tensions will this bring into their relationship?